Does umbrella branding really work? Investigating cross-category brand loyalty - Nadja Silberhorn; Lutz Hildebrandt (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
Numerous studies on the drivers of brand extension success [Aaker and Keller, 1990, Broniarczyk and Alba, 1994, Hem et al., 2003, Völckner and Sattler, 2006] found evidence that parent-brand characteristics and the fit between parent brand and transfer product are the main and most influential factors driving brand extension success. However, the ability of a brand to transfer its brand loyal customers from the parent to the extension category has been widely neglected. Brand loyalty can be regarded as a consequence of the underlying assumption of customers transferring their quality perceptions, their brand knowledge, and their experience with the brand from one category to the other [Erdem and Swait, 1998]. We find empirical evidence that consumers who are loyal to the brand in the leading (parent) product category show a higher probability to be loyal to that same brand in another (extension) category compared to those consumers who are not loyal in the leading category. Moreover, as the overall success of the extension includes positive retroactive effects of the extension product on the parent product or brand [Erdem, 1998], the arising question is whether there are differences between extension product categories regarding their attachment to the parent category and their ability to stimulate brand loyal purchases in the parent category, i.e., speaking of 'leader' and 'follower' categories in terms of brand loyal purchase behavior. This might even hold true for the relationship of any two categories the brand competes.
Keywords: M31; C43; 330; cross-category brand loyalty; loyalty leverage index; share of category requirements; Markentransfer; Markentreue; Konsumentenverhalten; Konsumgut; Schätzung; Deutschland